Welfare to work in contemporary European welfare states : legal, sociological and philosophical perspectives on justice and domination - Eleveld Anja (Policy Press, 2020)
With welfare to work programmes under intense scrutiny, this book ranges widely across Europe to review existing policies and explore future ones. It shows how many schemes do not adequately address social rights and lived experiences, and consider alternatives based on theories of non-domination.